Islamic Legal Perspectives on the Meja Waris Wedding Contribution Tradition in Jambi - Rajali; Zeni Sunarti; Nilfatri; Kuswanto; Kurniawan (Kartika: Jurnal Studi Keislaman, 2025)
This study explores the “meja waris” tradition, a form of collective wedding contribution practiced in Teluk Dawan Village, Tanjung Jabung Timur Regency, Jambi Province. The tradition embodies strong social values of solidarity and mutual cooperation, yet it raises academic concerns due to its potential tension with Islamic legal principles. The research aims to analyze the socio-cultural significance of the “meja waris” practice and to examine its conformity with Islamic law based on the perspectives of traditional leaders, religious leaders, community figures, and local residents. This study adopts a qualitative approach, utilizing in-depth interviews, direct observation, and documentation. Data validity was reinforced through triangulation to ensure accuracy and reliability. Findings reveal that the “meja waris” tradition serves as a social mechanism to reduce the financial burden of wedding ceremonies, reinforcing social capital within the community. However, its transformation into a binding norm that demands reciprocity has the potential to contradict Islamic legal values, particularly when coercion undermines sincerity and voluntarism. From an Islamic legal perspective, the practice remains permissible when grounded in ikhlāṣ (sincerity), tabarru‘ (voluntary giving), and ta‘āwun (mutual assistance), but becomes problematic when enforced as a social obligation. The study concludes by emphasizing the need to reinterpret and contextualize the “meja waris” tradition in accordance with Islamic values, with active involvement from the village government, religious and traditional authorities, community leaders, and academic institutions. Such collaboration is essential to preserve the tradition while ensuring alignment with Islamic legal and ethical principles.